The Impact of Celebrity’s Field of Expertise on Consumer Perception - Munasinghe, A.A.S.N; Bernard, D.T.K.; Samarasinghe, H.M.U.S.R.; Gamhewa, S.R.N.; Sugathadasa, Sajith; Muthukumara, T.C. (International Review of Management and Marketing, 2019)
The use of celebrity based endorsements in advertising has started receiving increased attention over the past few decades due to the glamour and the popularity added in promotions is one of the most salient aspects used in promoting a brand. A vast variety of celebrities, regardless of the respective field they belong to, have started endorsing number of brands and rarely fails in capturing the consumer attention. Although, attention and attraction based objectives are achieved via these celebrities, the need affecting the consumer perception remains vital as it aids in persuading the customers to convert their purchase intention to a purchase decision. However, the impact on consumer perception with regard to the endorsements by celebrities who does not have a relevance to the endorsed product is still a question to be probed in majority of the instances. Therefore, this study carried out with the intention of identifying the relationship between the celebrities field of expertise and consumer perception, takes up a quantitative approach with the application of chi-square test of independence in determining the association particularly with reference to the personal care product categories that exist in the Sri Lankan market. Keywords: Consumer perception, Endorsements, Personal care product categories, source JEL Classification: M3 DOI: https://doi.org/10.32479/irmm.7415